The effects of language skills, content and mother tongue on students' writing: a case study of part 3 students of UiTM Johor / Fazdilah Md. Kassim - Md. Kassim, Fazdilah (2009)
Learning and developing writing skills are considered a difficult task which makes the ability to write well even harder to be mastered. Previous researches done on students’ writing focused more on theories, attitudes, feedbacks and errors (Myles, 2002; Noriah et. al., 2008). Studies on factors that influence students’ writing specifically the effects of language skills, content and mother tongue are still relatively scarce in writing research. Thus, the present case study investigated on the ways these factors (language skills, content and mother tongue) affected students’ performance in writing in the case of English as a second language. Also, lecturers’ awareness was examined in confirming these effects existed in the writing process. Two types of instruments namely narrative responses were used on six student respondents and semi-structured interview was used on two lecturer respondents and selected through non-probability purposive sampling. The findings indicated that all three factors affected students’ poor performance in writing. The data analysis from student respondents’ showed that these students faced problems in writing but unable to identify the variables that affected them until they did the study. The results from the lecturers confirmed of the existence of those effects on students’ writing and a high level of awareness was identified through their ways of trying to rectify the problems. From the previous findings, the researcher then managed to identify how the effects influenced students’ writing in determination to guide instructors with better teaching in helping students become excellent writers. In conclusion, despite the many teaching and learning of writing skills, students still cannot escape from being influenced by these factors (language skills, content and mother tongue) when composing leading to poor performance in their writing.